Combination Therapy in Pulmonary Arterial Hypertension: Gleaning a Practical Approach from the Randomized Trials - Booth, David C. (International Journal of Angiology, 2019)
In the past decade, combination therapy in pulmonary arterial hypertension (PAH) has evolved from something PAH practitioners felt almost compelled to do, notwithstanding the absence of data, to a strategy proven by well-conducted randomized clinical trials. Whereas in the past, PAH treatment was limited to parenteral epoprostenol; today multiple drugs administrable either parenterally, inhaled, or orally have expanded the options for treating PAH patients. The SERIPHIN, AMBITION, and GRIPHON trials and emerging findings in FREEDOM-EV confirm the validity of a combined-therapy approach. Data from these trials in which either combined therapy was planned or an agent was added to background therapy have demonstrated significant reduction in the progression of disease and are on the cusp of demonstrating survival benefit. Combination therapy may be started simultaneously in some cases, but in many cases a stepped approach to initiating a second, or third, agent is better tolerated. Trials of all the specific combinations of drugs may not be possible, but a continuing trend toward treating PAH with multiple agents is likely. Currently, Food and Drug Administration-approved agents are predominantly pulmonary vasodilators acting through different pathways, with minimal impact on progression of the proliferative pulmonary arteriopathy that is the key pathologic finding in PAH. It is to be hoped that treatment strategies that result in halting progression and substantial reversal of pulmonary arteriolar obstruction will soon be discovered and available.
Keywords: pulmonary arterial hypertension; combination PAH drug therapy; WHO Group 1 PAH; macitentan; ambrisentan; tadalafil; selexipag